Exploitation of Hunting and Fishing Tourism in Galați County, Romania - Camară Gabriel (Present Environment and Sustainable Development, 2016)
Galați county is a geographical area that is less valued in terms of tourism, but which benefits by a natural tourism potential. The aim of this study is to identify the potential and the activities of the hunting and fishing tourism. Exploitation of hunting and fishing activities in touristic aim is only partial because of the lack of touristic infrastructure and the lack of collaboration with various travel agencies from this branch of tourism. Proposals that would help the future development and improvement of tourism activity are from “wildlife watching tourism” domain: capturing images with the camera, observing the behavior of hunting species without affecting them, providing information for those interested in the hunting behavior and life fauna, creating a wildlife museum and last but not least, upgrading the transport infrastructure.